Introduction of Credit Derivatives and Valuation of Credit Default Swap - Han, Lu (2006)
The credit derivative market was established at the beginning of the 1990s since the emergence of credit derivatives fits the rapid development of the whole derivatives market. However, compare to other derivative market, this market is still small and incomplete. As with other derivatives, credit derivatives can be used to either take more risk or hedge it, hence various credit derivatives instruments are accepted and widely used by market participants such as banks, insurance companies, etc. this paper aims to provide a general insight into credit derivative market, explore some of the interesting issues relates to different credit derivatives products. The analyis conducted in this paper gives a basic understanding of mechanism of credit derivatives and how credit default swap, the most popular credit derivative in the market, can be valued.